Control of Shell Morphology in p–n Heterostructured Water‐Processable Semiconductor Colloids: Toward Extremely Efficient Charge Separation. Issue 2 (14th November 2018) - Kim, Yu Jin; Schaller, Richard D.; Fry, Harry Christopher
Abstract: This article describes p–n heterostructured water‐borne semiconductor naonoparticles (NPs) with unique surface structures via control of shell morphology. The shell particles, comprising PC60–[6, 6]‐phenyl‐C61‐butyric acid methyl ester (PC61 BM) composite, having n‐type semiconductor characteristics, notably influence the charge carrier behavior in the core–shell NPs. A one‐ or two‐phase methodology based on a PC60 surfactant‐water phase and PC61 BM n‐type semiconductor‐organic phase provides highly specific control over the shell structure of the NPs, which promote their superior charge separation ability when combined with poly‐3‐hexyl‐thiophene (P3HT). Moreover, the resulting water‐borne NP exhibits shell morphology‐dependent carrier quenching and stability, which is characterized via luminescence studies paired with structural analysis. Corresponding to the results, outstanding performances of photovoltaic cells with over 5% efficiency are achieved. The results suggest that the surrounding shell environments, such as the shell structure, and its electronic charge density, are crucial in determining the overall activity of the core–shell p–n heterostructured NPs. Thus, this work provides a new protocol in the current fields of water‐based organic semiconductor colloids. Abstract : The PC60–PC61 BM composite shell particles synthesized via a one‐ or two‐phase methodology afford a higher n‐type electronic charge density than pure PC60, which allows extremely efficient charge separation ability when they combined with p‐type core particles. The core–shell water‐borne nanoparticles show outstanding photovoltaic performances with over 5% efficiency.